(untitled) (Environment & Health, 2018)
Objective: We established the optimum dose-time parameters of chlorine dioxide application in traditional water treatment technology providing a high quality and a safety of drinking water. Materials and methods: For the primary disinfection of the Dnipro river water, chlorine dioxide was used in a range of 2.0–4.0 mg/dm3 in aluminum sulfate coagulant (140.0 mg/dm3) and TR650 flocculant (0.3 mg/dm3). Secondary disinfection was carried out with chlorine dioxide at a dose of 0.5 mg/dm3. The analysis of water by physical-and-chemical microbiological parameters before and after treatment was carried out with an additional determination of residual chlorine dioxide, chlorites, chlorates, and trihalomethanes by generally accepted methods according to the State Sanitary Norms and Rules 2.2.4-171-10. Results: The quality of river water after treatment with chlorine dioxide and with the participation of coagulant, flocculant, sedimentation, and filtration was improved at all doses of chlorine dioxide. At a minimum dose of chlorine dioxide of 2.0 mg/dm3, the parameters of turbidity, water colour, permanganate oxidability, and iron were decreased by 82.6%, 86.3%, 65.0%, and 18.7%, respectively. In addition, there was a decrease in indicator microorganisms by 93-100%. It indicates a high bactericidal activity of chlorine dioxide as a disinfectant. In water, there is no formation of chlorites, dangerous for human organism, and aluminum in excessive concentrations. Among 7 investigated volatile chloro-organic compounds, only chloroform and bromodichloromethane were detected in quantities not exceeding the hygienic standard. Conclusions: Experimental investigations of the river water treatment, according to the traditional technology with the use of chlorine dioxide, showed its high effectiveness in organic and microbial contamination of the river Dnipro. Even at the low doses of chlorine dioxide of 2.0 mg/dm3, there was a high bactericidal effect in sanitary-indicative microorganisms (93-100%). Chlorine dioxide was confirmed to have a low ability to form highly toxic volatile organochlorine compounds (trihalomethanes) that were determined on the basis of chloroform (the foreground compound) at the level of 1.0-3.0 mg/dm3. It is advisable to continue the experiment at the river pipe-line, modelling increased levels of organic contamination in water that can cause an increase of the by-products of the disinfection in water, first of all dangerous chlorites, formed during the treatment of water with chlorine dioxide.